Transparency and Trust: Building Strong Relationships Through Open Communication PT Pupuk Kalimantan Timur - Kurnia, Renita; Wulung, Lingga Angling; Cindoswari, Ageng Rara (Persatuan Wartawan Indonesia, 2024)
This research focuses on the implementation of PT Pupuk Kalimantan Timur when it builds strong relationships with its public through open communication. Public trust and transparency are crucial in overcoming the consequences of the explosion at Factory 5 of PT Pupuk Kalimantan Timur. These attract media attention because of their significant impact on its factory operations. The research method used in this study is a qualitative case study. It collected data through 3 (three) stages: observation, interviews, and literature study. In this research, the data reduction, data presentation, and conclusion or verification stages are the three steps to assist the authors in the data analysis. The research results show that PT Pupuk Kalimantan Timur has applied principles of Excellence Public Relations Theory by prioritizing transparency, trust, and open communication to maintain its reputation and relationships with the public. It responded quickly, provided a transparent written response regarding the incident, and actively monitored the dynamics of public opinion. PT Pupuk Kalimantan Timur's steps include stakeholder involvement, collaboration in designing PR programs, and effective online reputation management. Evaluation of these steps shows its awareness of the importance of continuous learning and adaptation to maintain its reputation and image. Therefore, PT Pupuk Kalimantan Timur's transparent, open communication approach reflects its commitment to achieving PR principles effectively in facing the challenges they are encountering.